Pricing sin stocks: Ethical preference vs. risk aversion - Stefano Colonnello; Giuliano Curatola; Alessandro Gioffré (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
We develop a model that reproduces the average return and volatility spread between sin and non-sin stocks. Our investors do not necessarily boycott sin companies. Rather, they are open to invest in any company while trading off dividends against ethicalness. We show that when dividends and ethicalness are complementary goods and investors are sufficiently risk averse, the model predicts that the dividend share of sin companies exhibits a positive relation with the future return and volatility spreads. Our empirical analysis supports the model's predictions.
urn:nbn:de:hebis:30:3-466812
Keywords: D51; D91; E20; G12; 330; Asset Pricing; General Equilibrium; Sin Stocks